Efficacy and Safety of 4-Weekly Docetaxel for Castration-Resistant Prostate Cancer. (16th March 2021) - Yamashita, Takuya; Shiota, Masaki; Machidori, Asako; Kobayashi, Satoshi; Matsumoto, Takashi; Monji, Keisuke; Kashiwagi, Eiji; Takeuchi, Ario; Takahashi, Ryosuke; Inokuchi, Junichi; Shiga, Ken-ichiro; Yokomizo, Akira; et al.
Abstract: We investigated the efficacy and safety profiles of 4-weekly docetaxel for castration-resistant prostate cancer. Patients treated with ≥2 courses of docetaxel chemotherapy (median, 70 mg/m 2 ) between 2008 and 2018 were included. Among 125 Japanese men, 40 (32.0%) and 85 (68.0%) were treated with 3-weekly and 4-weekly regimens, respectively. In the 4-weekly regimen, the risks of progression, treatment failure, and any-cause mortality were comparable to those in the 3-weekly regimen. The incidences of severe adverse events were also similar between the 3-weekly and 4-weekly regimens. These data suggest that the 4-weekly regimen may be an acceptable option for selected patients.